Direct asymmetric ruthenium-catalyzed reductive amination of alkyl-aryl ketones with ammonia and hydrogen - Gallardo-Donaire, Joan; Hermsen, Marko; Wysocki, Jędrzej; Rominger, Frank; Trapp, Oliver; Hashmi, A. Stephen K.; Comba, Peter; Schaub, Thomas (Journal of the American Chemical Society, 2018)
The asymmetric ruthenium-catalyzed reductive amination employing ammonia and hydrogen to primary amines is described. Here we demonstrate the capability of our catalyst to perform a chemo- and enantioselective process while using simple ammonia gas as a reagent, one of the most attractive and industrially relevant nitrogen sources. The presence of a catalytic amount of ammonium iodide was essential for obtaining good yields and enantioselectivities. The mechanism of this reaction was investigated by DFT and we found a viable pathway that also explains the trend and magnitude of enantioselectivity through the halide series in good agreement with the experimental data. The in-depth investigation of substrate conformers during the reaction turned out to be crucial in obtaining an accurate prediction of the enantioselectivity. Furthermore, we report the crystallographic data of the chiral [Ru(I)H(CO)((S,S)-f-binaphane)(PPh3)] complex, which we identified as the most efficient catalyst in our investigation.